The Value of Radiotherapy for Advanced Non-Small Cell Lung Cancer With Oncogene Driver-Mutation - Cui, Jinfeng; Li, Li; Yuan, Shuanghu (Frontiers in Oncology, 2022)
Targeted tyrosine kinase inhibitors (TKIs) has been widely used in the treatment of advanced non–small-cell lung cancer (NSCLC) patients with oncogene driver-mutation. TKIs have replaced cytotoxic chemotherapy as first-line treatment, which make advanced NSCLC patients with oncogene driver-mutation have longer survival time. However, TKIs resistance affects its long-term efficacy. The ability of TKIs to permeate into cerebrospinal fluid (CSF) also seemed limited. Only a small fraction of the plasma levels could be achieved in cerebrospinal fluid at standard doses. Therefore, the efficacy of TKIs monotherapy may be limited for patients with brain metastasis. Some studies showed that radiotherapy could reduce TKI resistance and destroy the integrity of blood brain barrier (BBB), which suggested that radiotherapy and targeted therapy may have a synergistic effect for advanced oncogene driver-mutated NSCLC patients. This article reviews the value of radiotherapy in those patients.